Compassion and bioethics - Washburn C., Jimmy (Acta Bioethica, 2004)
Human pain and suffering affect our lives. Moreover, mediatic efficiency has contributed to let foreign suffering enter our homes through spectacular presentations. The subject we want to stress here is comprehension of human finitude and bioethics' response to it. We shall try to establish relationships between compassion and the principle of beneficence. In order to secure patients' wellbeing -strangers most of them- with an attitude and an ethics' perception, that is not object of a normative obligation.